2014
DOI: 10.1161/circulationaha.113.004168
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Incident Venous Thromboembolism on Risk of Arterial Thrombotic Diseases

Abstract: Background-Growing evidence supports an association between venous thromboembolism (VTE) and arterial thrombotic diseases (ie, myocardial infarction and ischemic stroke). We aimed to study the association between VTE and future arterial events and to determine the population attributable risk of arterial events by VTE in a large prospective cohort recruited from the general population. Methods and Results-In 1994 to 1995 and 1993 to 1997, 81 687 subjects were included in the Tromsø Study and in the Diet, Cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 53 publications
3
40
1
Order By: Relevance
“…37,38 Numerous observational studies have shown an independent association between arterial and venous thrombotic diseases. [10][11][12][13][14][15][16][17][18] However, the risk estimates for MI and VTE by FHMI in our study were similar in the traditional Cox model and in the cause-specific Cox model, implying that the associations between FHMI and MI and VTE were not affected by a direct interaction between VTE and MI. From a public health perspective, we found FHMI to be a considerable risk factor for VTE with a predictive value comparable with family history of VTE, 39 explaining 13% of the VTE events in the study population.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…37,38 Numerous observational studies have shown an independent association between arterial and venous thrombotic diseases. [10][11][12][13][14][15][16][17][18] However, the risk estimates for MI and VTE by FHMI in our study were similar in the traditional Cox model and in the cause-specific Cox model, implying that the associations between FHMI and MI and VTE were not affected by a direct interaction between VTE and MI. From a public health perspective, we found FHMI to be a considerable risk factor for VTE with a predictive value comparable with family history of VTE, 39 explaining 13% of the VTE events in the study population.…”
Section: Discussionsupporting
confidence: 54%
“…[10][11][12][13][14][15][16][17][18] However, growing evidence supports the notion that atherosclerotic risk factors, including diabetes mellitus, hypertension, and dyslipidemia, are not associated with VTE. [19][20][21][22][23] Obesity and advancing age were the only shared risk factors for arterial and venous thrombosis in cohort studies, investigating the influence of atherosclerotic risk factors on risk of MI and VTE within the same population.…”
Section: Clinical Perspective On P 691mentioning
confidence: 99%
“…Women and young men with venous thromboembolism have higher risk of arterial thrombotic disease than those without venous thromboembolism in Tromsø's study. [13] Some cases with gastro-intestinal, hematological, and germinal system malignancy have been reported as having AMI. [12] Dieckmann, et al demonstrated that a majority patients diagnosed with testicular cancer and AMI did not have traditional atherosclerotic risk factors and coronary plaque.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of venous and arterial thrombotic diseases underlie traditional atherosclerotic risk factors such as advanced aged, obesity, hypertension, dyslipidemia, and diabetes. [13] The possible mechanism of both venous and arterial embolism may result from direct cancer vascular invasion, mucin-mediated thrombosis, intra-cardiac or intra-vascular embolization, activation of coagulation cascade by tissue factor, thrombin, inflammatory cytokines, and endothelial and platelet adhesion molecules. [12][13][14]17] Other non-traditional risk factors for venous and arterial thrombosis were increased level of homocysteine, coagulation factors VIII, IX, XI, and von Willebrand factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation